PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE DALAM PENYELENGGARAAN REFORMA AGRARIA DI INDONESIA - Muhammad Ilham Arisaputra (Universitas Airlangga, 2013)
Agrarian reform is one of solutions to overcome the poverty. The agrarian reform needs a political commitment from the government. In addition, agrarian information is important to figure out the problems and its potential to overcome the problems. Agrarian reform can not depend on the authority and political power of the government only, it also needs the involvement of the community and other stakeholders. In the context of regional authonomy, the authority of agrarian reform will be the authority of the local government, therefore the involvement of the community in every stage is necessary. National Planning for Agrarian Reform Programme should be conformed with the characteristics of the region and the inputs from the stakeholders, since they understand the situation and the agrarian problems in the region.Keywords: agrarian reform, stakeholders, landreform.